# What is a correct first step in solving the inequality -4(3 - 5x) ≥ -6x + 9?

-12 - 20x ≤ -6x + 9

-12 - 20x ≥ -6x + 9

-12 + 20x ≤ -6x + 9

-12 + 20x ≥ -6x + 9

**Solution:**

The given inequality is

-4(3 - 5x) ≥ -6x + 9

Using the multiplicative distributive property

-12 + 20x ≥ -6x + 9

By rearranging the variables and constants

20x + 6x ≥ 9 + 12

By adding on both sides

26x ≥ 21

Dividing both sides by 26

26x/26 ≥ 21/26

x ≥ 21/26

Therefore, the correct first step is -12 + 20x ≥ -6x + 9.

## What is a correct first step in solving the inequality -4(3 - 5x) ≥ -6x + 9?

**Summary:**

The correct first step in solving the inequality -4(3 - 5x) ≥ -6x + 9 is -12 + 20x ≥ -6x + 9.

Math worksheets and

visual curriculum

visual curriculum